ANALISIS DAYA SAING EKSPOR TEKSTIL INDONESIA KE AS MENGGUNAKAN REVEALED COMPARATIVE ADVANTAGE (RCA) - Utami, Eva Yuniarti; Pratama, Arizal Putra; Destiana, Irna Dwi; Muslim, Istianah; Wulandari, Kartika (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
This research focuses on analyzing the competitiveness of Indonesian textile products in the United States market, one of the main export destinations for Indonesian textiles. The purpose of this study is to assess the comparative advantage of Indonesian textile products using the Revealed Comparative Advantage (RCA) method. The research employs secondary data obtained from sources such as the International Trade Centre’s Trade Map (2023), Ministry of Trade (2022), and Ministry of Industry (2023). The results of the RCA analysis reveal that several textile products, such as women’s knitted blouses and men’s suits, show high RCA values, indicating strong competitive advantages. However, challenges such as dependency on imported raw materials, inconsistent product quality, and limited innovation and research and development (R&D) hinder Indonesia's competitiveness in global markets. Furthermore, more than 70% of Indonesia's textile exports to the United States are channeled through intermediaries, reducing control over pricing and marketing strategies. This study recommends strategies to enhance Indonesia's textile competitiveness, such as reducing dependence on imported raw materials, improving product quality control, and increasing investment in innovation and R&D. Strengthening direct distribution networks to major markets like the United States and Europe is also essential for improving competitiveness.